Assessment of grain quality in terms of functional group response to elevated [CO2], water, and nitrogen using a meta‐analysis: Grain protein, zinc, and iron under future climate. Issue 13 (22nd June 2019) - Al‐Hadeethi, Ikhlas; Li, Yan; Odhafa, Abdul Kareem H.; Al‐Hadeethi, Hanan; Seneweera, Saman; Lam, Shu K.
Abstract: The increasing [CO2 ] in the atmosphere increases crop productivity. However, grain quality of cereals and pulses are substantially decreased and consequently compromise human health. Meta‐analysis techniques were employed to investigate the effect of elevated [CO2 ] (e[CO2 ]) on protein, zinc (Zn), and iron (Fe) concentrations of major food crops (542 experimental observations from 135 studies) including wheat, rice, soybean, field peas, and corn considering different levels of water and nitrogen (N). Each crop, except soybean, had decreased protein, Zn, and Fe concentrations when grown at e[CO2 ] concentration (≥550 μmol/mol) compared to ambient [CO2 ] (a[CO2 ]) concentration (≤380 μmol/mol). Grain protein, Zn, and Fe concentrations were reduced under e[CO2 ]; however, the responses of protein, Zn, and Fe concentrations to e[CO2 ] were modified by water stress and N. There was an increase in Fe concentration in soybean under medium N and wet conditions but nonsignificant. The reductions in protein concentrations for wheat and rice were 5%–10%, and the reductions in Zn and Fe concentrations were 3%–12%. For soybean, there was a small and nonsignificant increase of 0.37% in its protein concentration under medium N and dry water, while Zn and Fe concentrations were reduced by 2%–5%. The protein concentration of field peas decreased by 1.7%, and the reductions in Zn and Fe concentrations were 4%–10%. The reductions in protein, Zn, and Fe concentrations of corn were 5%–10%. Bias in the dataset was assessed using a regression test and rank correlation. The analysis indicated that there are medium levels of bias within published meta‐analysis studies of crops responses to free‐air [CO2 ] enrichment (FACE). However, the integration of the influence of reporting bias did not affect the significance or the direction of the [CO2 ] effects. Abstract : Meta‐analysis techniques were employed to investigate the effect of elevated [CO2 ] on protein, zinc (Zn), and iron (Fe) concentrations of major food crops considering different levels of water and nitrogen application (N). Grain protein, Zn, and Fe concentrations are reduced at e[CO2 ], but their responses are modified by factors, such as water stress; N.Bias in the dataset was assessed using a regression test and rank correlation. The analysis indicated that there are medium levels of bias within published meta‐analysis studies of crops responses to free‐air [CO2 ] enrichment (FACE).